2019
DOI: 10.2139/ssrn.3471042
|View full text |Cite
|
Sign up to set email alerts
|

Investment-Cash Flow Sensitivity and Financing Constraints: Study of Pakistani Business Group Firms

Abstract: A large discrepancy exists on the use of the investment-cash flow sensitivity as a measure of financing constraints of firms. We examine this discrepancy by considering business group affiliated firms in Pakistan. The study includes 58 group affiliated firms and 32 non-group affiliated firms listed on the Karachi Stock Exchange during 2006-2010. Results of OLS and 2SLS shows a positive investment-cash flow sensitivity for business group affiliated firms and negative investment cash flow sensitivity for nongrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Leverage means the firms can easily obtain loans in the times of financial need. The B.G AFs are having higher leverage relatively NAFs (Mehmood and Farid Hasnu, 2019). B.G AFs have easy access to the external financial markets (Aggarwal et al, 2019).…”
Section: Leveragementioning
confidence: 99%
See 3 more Smart Citations
“…Leverage means the firms can easily obtain loans in the times of financial need. The B.G AFs are having higher leverage relatively NAFs (Mehmood and Farid Hasnu, 2019). B.G AFs have easy access to the external financial markets (Aggarwal et al, 2019).…”
Section: Leveragementioning
confidence: 99%
“…Conversely, NAFs are high risky and face more changing threats thats why study is more emphasized on AFs and NAFs of Pakistan. The study of Mehmood and Farid Hasnu (2019) suggested that if the credit is a main problem for the entrepreneur, then the firm is financially constrained and vice versa. Their results confirmed that the firms having a positive sensitivity of cash holding and cash flows are more likely to be the financially constrained.…”
Section: Multiple Linear Regression Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Di, Shaiban, and Hasanov (2021), higher level of dividend yields results in high market value, thus resulting in stable stock market prices, resulting in lower volatilities. Whereas high fluctuations in the dividend yield, lower level of shareholders wealth and low dividend payout ratio results in high level of stock market volatility (Liaqat, Nazir, & Ahmad, 2019;Mehmood & Farid Hasnu, 2019). 2015) by employing the model presented by (Baskin, 1989) reported that dividend payments are inversely associated with SPV in context of PSX.…”
Section: Literature Reviewmentioning
confidence: 99%